PENGARUH KNOWLEDGE MANAGEMENT DAN ORGANIZATIONAL CULTURE TERHADAP KINERJA BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT KEPOLISIAN RESOR KENDARI - Suhirno Suhirno; Rahmat Madjid; Yusuf Yusuf (Pascasarjana Universitas Halu Oleo, 2020)
Along with the current progress and development of the Kendari Resort Police to maximize knowledge and build an effective organizational culture in order to create better work results and quality of personnel work, so that the existence of Bhabinkamtibmas personnel in the midst of society can create security and order in the jurisdiction of the Kendari Resort Police.This study aims to determine and analyze the effect of Knowledge Management and organizational culture on the performance of members of the Kendari District Police Bhabinkamtibmas. The population of this study was all members of the Kendari District Police Bhabinkamtibmas of 80 people and all of them were sampled. The analytical tool used is partial least square with the Smart PLS program version 3.0 while the data collection method used questionnaires, documentation and interviews.Based on the results of the study it was concluded that: (1) knowledge management had a positive and significant effect on the performance of the Kendari District Police Bhabinkamtibmas (2) organizational culture had a positive and significant effect on performance of the Kendari District Police Bhabinkamtibmas.